Development and Validation of the Political Skill Inventory - Ferris, Gerald R.; Treadway, Darren C.; Kolodinsky, Robert W.; Hochwarter, Wayne A.; Kacmar, Charles J.; Douglas, Ceasar; Frink, Dwight D. (Journal of Management, 2005)
The present research was developed to examine the conceptualization and measurement of the political skill construct and to provide validation evidence for the Political Skill Inventory (PSI). The results of three investigations, involving seven samples, are reported that demonstrate consistency of the factor structure across studies, construct validity, and criterion-related validity of the PSI. As hypothesized, political skill was positively related to self-monitoring, political savvy, and emotional intelligence; negatively related to trait anxiety; and not correlated with general mental ability. Also, the PSI predicted performance ratings of managers in two samples. Implications of these findings and directions for future research are provided.